Infant digital fibroma: case report - Romero Rojas, Nery (2011)
Infant digital fibroma or inclusion body fibromatosis is a rare disorder consisting in a benign proliferative process of myofibroblast cells that in histopathology show cytoplasm inclusion bodies. Nodules develop mainly in fingers and toes of infants. There is high recurrence but spontaneous regression without treatment has also been reported. We present the case of a 4 month-old boy showing a 1.5 x 1.3 x 0.6 cm nodule in the third finger of the right hand. Histological examination revealed spindled tumor cells containing characteristic intracytoplasmic inclusion bodies that stained with vimentin, muscle specific actin and desmin.